Hubungan Penerimaan Kepuasan Body Image Dengan Kepercayaan Diri Pada Siswa-Siswi SMP Negeri 1 Wonogiri - Silvia Belva Dristi; Gendon Barus (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2024)
This research uses correlative quantitative research, with the subject of students of Junior High School Negeri 1 Wonogiri. The sample in this study amounted to 80 samples. The process of collecting data by distributing questionnaires directly using google forms with statements that use a likert scale. On the body image satisfaction acceptance scale there are 33 valid items with an Alpha Cronbach reliability index of 0.788. The self-confidence scale has 36 valid items with an Alpha Cronbach reliability index of 0.911. The data analysis technique used is descriptive categorization technique, normality test, linearity test, hypothesis test and correlation test.The results in this study show: (1) there is a significant positive relationship between the variables, (2) the level of body image satisfaction acceptance in the moderate category with a percentage of 43%, (3) the level of self-confidence is classified in the high category with a percentage of 50%, (4) there are 2 items in the body image satisfaction acceptance scale that are identified as low with a percentage of 6%, so they are used as guidance topics, (5) there are no items in the self-confidence scale that are identified as low to be used as guidance topics.